NURSING CARE IN ADULT PATIENT WITH SUPRARECTAL AMPUTATION - MARIUXI JOHANNA ZURITA DESIDERIO, VILMA ROCIO QUIJIJE CHAVEZ, BLANCA JAHAYRA MUÑOZ TORRES, GLADYS TASINCHANA BASTIDAS (South Eastern European Journal of Public Health, 2025)
This study examines nursing care for an adult patient with supracondylar amputation associated with type 2 diabetes mellitus. The research highlights the physical, emotional, and social challenges faced by the patient after the amputation, emphasizing the importance of comprehensive and multidisciplinary care. Using Marjorie Gordon's functional patterns model, key intervention areas were identified, including pain management, self-care education, and adaptation to a new physical reality. The patient, a 58-year-old man, presented complications such as malnutrition, anemia, and renal impairment, complicating recovery. Strategies focused on infection monitoring, physical rehabilitation, and emotional support were implemented to promote independence and quality of life. The results show significant improvements in infection control, mobility, and psychosocial adaptation. Furthermore, the study highlights the need for structured education for patients and their families, aimed at preventing future complications and promoting overall well-being. This study underscores the crucial role of nursing in the rehabilitation of patients with amputations, proposing innovative and collaborative approaches that integrate medical, emotional, and social aspects.